LiverZap: a chemoptogenetic tool for global and locally restricted hepatocyte ablation to study cellular behaviours in liver regeneration - Ambrosio, Elizabeth M.G.; Bailey, Charlotte S.L.; Unterweger, Iris A.; Christensen, Jens B.; Bruchez, Marcel P.; Lundegaard, Pia R.; Ober, Elke A. (Development, 2024)
The liver restores its mass and architecture after injury. Yet, investigating morphogenetic cell behaviours and signals that repair tissue architecture at high spatiotemporal resolution remains challenging. We developed LiverZap, a tuneable chemoptogenetic liver injury model in zebrafish. LiverZap employs the formation of a binary FAP-TAP photosensitiser followed by brief near-infrared illumination inducing hepatocyte-specific death and recapitulating mammalian liver injury types. The tool enables local hepatocyte ablation and extended live imaging capturing regenerative cell behaviours, which is crucial for studying cellular interactions at the interface of healthy and damaged tissue. Applying LiverZap, we show that targeted hepatocyte ablation in a small region of interest is sufficient to trigger local liver progenitor-like cell (LPC)- mediated regeneration, challenging the current understanding of liver regeneration. Surprisingly, the LPC response is also elicited in adjacent uninjured tissue, at up to 100 μm distance to the injury. Moreover, dynamic biliary network rearrangement suggests active cell movements from uninjured tissue in response to substantial hepatocyte loss as an integral step of LPC-mediated liver regeneration. This precisely targetable liver cell ablation tool will enable the discovery of key molecular and morphogenetic regeneration paradigms.
Created from Fastlane, Scopus look-up
Keywords: Biliary network; Liver progenitor cells (LPCs); Liver regeneration; Local injury; Morphogenesis; Optogenetic hepatocyte ablation; Zebrafish